Reforming the judicial appointment process in Malaysia - Shuaib, Farid Sufian (2010)
Malaysian judges’ reputation had suffered beginning from the removal of Tun Salleh Abas, the former Lord President. Subsequent handling of Anwar Ibrahim’s prosecutions and added by accidental holidaying together of a former Chief Justice with a prominent lawyer do not help in mending its standing. The former Prime Minister Abdullah Badawi had taken steps to patch up the situation by granting ex gratia payments to Tun Salleh Abas and other ex-judges. Following the report by the Commission of Inquiry on the alleged fixing up by third parties of judicial appointment (or popularly known as the VK Lingam Tape Commission), a Judicial Appointments Commission was established. This paper seeks to examine the commission and to consider whether such a commission could contribute significantly in the creation of an independent and competent judiciary. Lesson learned from other countries such as England and Australia will be considered.